Energy Storage Optimization Configuration and Operation for High-Altitude Power Grids Considering Power Supply Guarantee and Clean Energy Utilization - Chen, Yunyao; Li, Bin; Deng, Xianlin; Chen, Yuzhou; Zhang, Qingyuan; Liao, Qingxi (Distributed Generation & Alternative Energy Journal, 2025)
With the continuous advancement of the Goal of Emission Peak & Carbon Neutrality, the penetration of clean energy in the new power system is in creasing day by day. The randomness, intermittency, and volatility associated with this development make power supply guarantee and clean energy utilization challenges even more severe. Insufficient power consumption capacity in the power system can lead to wind and solar curtailment, while power shortages on the generation side may cause load shedding and power supply insufficiency. The configuration of electrochemical energy storage is an effective method to smooth out renewable energy fluctuations and alleviate supply-demand imbalances. This paper proposes an energy storage optimization configuration and operation strategy that considers both power supply guarantee and clean energy utilization. First, taking the power grid of a high-altitude region as the research object, the two key demands of power supply guarantee and clean energy utilization are identified, and three indicators – clean energy utilization, load shedding, and power supply insufficiency – are formulated. Next, based on historical data, typical operational scenarios for local photovoltaic power generation units and load are clustered. Using this clustering data, an upper-level energy storage planning configuration is made. The resulting configuration is then applied to the lower-level operational model, which incorporates power supply guarantee and clean energy utilization constraints, to build a two-layer model for energy storage optimization and operation. Finally, the feasibility and effectiveness of the proposed strategy are verified through a practical power system in a high-altitude region of western China. Compared to configuring energy storage independently, considering both power supply guarantee and clean energy utilization in the system regulation can significantly enhance the clean energy utilization rate and power supply guarantee level of the regional grid while minimizing the unit cost of mitigating power shortages and solar curtailment. The local grid can adjust the range of power supply guarantee and clean energy utilization indicators according to actual needs to balance the economic and social benefits of the grid.